Adult Renal Transplantation in a Patient 28 Years after Heart Transplantation as a Neonate for Hypoplastic Left Heart Syndrome - Joseph Licata; Shane Michael Roberts; Piotr Janicki; Dmitri Bezinover (Case Reports in Transplantation)
We present a case of kidney transplantation in a 28-year-old patient who received a heart transplant at 7 weeks of age due to hypoplastic left heart syndrome. The patient’s renal insufficiency was the result of chronic immunosuppression and hypertension. The almost 28-year-old graft demonstrated very good function. This patient represents as one of the longest pediatric cardiac graft recipients living without any significant functional limitations.